Important considerations for agile software development methods governance - Gandomani, Taghi Javdani; Zulzalil, Hazura; Abd Ghani, Abdul Azim; Md Sultan, Abu Bakar (Asian Research Publication Network, 2013)
After introducing Agile approach in 2001, several Agile methods were founded over the last decade. Agile values such as customer collaboration, embracing changes,iteration and frequent delivery, continuous integration, etc. motivate all software stakeholders to use these methods in their projects. Moving to Agile methods needs a huge change in organization and involved people. This change is a fundamental and critical mutation. The main issue is that Agile transition and governance action plan needs to consider different aspects of change related issues. Conduction a Grounded Theory study with participation of 37 Agile experts from 13 countries showed that software companies should consider three main factors before inception of transformation action plan: Adoption styles, Method selection and Awareness of challenges and constraints. These fundamental considerations encompass many critical items for Agile movement and adoption process. However these items may lead to different results in different companies, but they should be studied in deep before any transition action plan.